Pokroky v karotické endarterektomii--prehledný referát - Pribán, V (Rozhledy v chirurgii, 2000)
Atherosclerosis of carotid artery, resulting in stenosis is a common cause of cerebral ischaemia. Ischaemic stroke is cause of death in 10% of patients and the leading cause of disability in adults. The risk of stroke increases with the degree of stenosis. The diagnosis of the degree of stenosis is performed by duplex sonography, MR-angiography, CT-angiography and conventional angiography. Carotid endarterectomy is a method of choice in the treatment in the case of high-grade carotid stenosis. The operation was introduced in 1953. Either regional or general anaesthesia is used for the operation. The different monitoring techniques are used for assessment of the need for shunting. Microsurgical technique enables perfect endarterectomy and fine arterial repair without need for patch grafting. Other techniques of the treatment for carotid stenosis, including carotid angioplasty with or without stenting are subject to the evaluation. Carotid endarterectomy is now the method of choice in the treatment of high-grade carotid stenosis.
Keywords: karotická endarterektomie; Endarterectomy, Carotid; Carotid Artery Diseases; lidé; nemoci arterie carotis; Humans